2014
DOI: 10.5847/wjem.j.issn.1920-8642.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Emergency bedside ultrasound for the diagnosis of pediatric intussusception: a retrospective review

Abstract: BACKGROUND: Ultrasound diagnosis of pediatric intussusception is feasible with limited operator training. The authors report the test characteristics of bedside ultrasound (BUS) for the diagnosis of pediatric intussusception at a single institution.METHODS: Inclusion criteria were: 1) patients of 0-18 years old were seen in the pediatric emergency department (ED) with a clinical presentation suspicious for intussusception; 2) BUS was performed to identify intussusception and bedside impression documented in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 12 publications
3
36
0
Order By: Relevance
“…In this study, POCUS performed by pediatric emergency physicians seemed highly reliable (sensitivity, 100%; specificity, 95.6%; and accuracy, 97.8%) and useful (positive likelihood ratio, 23.0; and negative likelihood ratio, 0) in detecting intussusception. A previous study also showed a high degree of accuracy with 100% sensitivity and 94% specificity, even though it enrolled only 49 patients, which was a relatively small number [9]. Among the 92 patients with "suspicious" POCUS results in this study, 22 were confirmed as false positives, with a relatively low positive predictive value of 76.1%.…”
Section: Discussionmentioning
confidence: 47%
“…In this study, POCUS performed by pediatric emergency physicians seemed highly reliable (sensitivity, 100%; specificity, 95.6%; and accuracy, 97.8%) and useful (positive likelihood ratio, 23.0; and negative likelihood ratio, 0) in detecting intussusception. A previous study also showed a high degree of accuracy with 100% sensitivity and 94% specificity, even though it enrolled only 49 patients, which was a relatively small number [9]. Among the 92 patients with "suspicious" POCUS results in this study, 22 were confirmed as false positives, with a relatively low positive predictive value of 76.1%.…”
Section: Discussionmentioning
confidence: 47%
“…In this study, POCUS performed by pediatric emergency physicians seemed highly reliable (sensitivity, 100%; specificity, 95.6%; and accuracy, 97.8%) and useful (positive likelihood ratio, 23.0; and negative likelihood ratio, 0) in detecting intussusception. A previous study also showed a high degree of accuracy with 100% sensitivity and 94% specificity, even though it enrolled only 49 patients, which was a relatively small number [7]. Among the 92 patients with "suspicious" POCUS results in this study, 22 were confirmed as false positives, with a relatively low positive predictive value of 76.1%.…”
Section: Discussionmentioning
confidence: 47%
“…Several studies have suggested that point-of-care ultrasound (POCUS) performed by pediatric emergency physicians could be a practical measure [6][7][8]. POCUS for detecting intussusception is relatively easy to learn and readily available in the ED [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been no agreement on what constitute as sufficient training for novice sonographers. The first study by Lam (Lam et al 2014) subjected the emergency physicians to a minimum 1 hr of didactic training on the use of bedside ultrasound using paediatric transducers. They did not go on to explain what the didactic training comprise of.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective review (Lam et al 2014) compared the accuracy of bedside ultrasound diagnosis of intussusception made by Emergency Physicians to the "formal" diagnostic study such as ultrasound, CT and barium enema performed in the Radiology Department. Out of 1631 of the medical records been reviewed in a single centre, 44 met the inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%